Does whole-body electrical muscle stimulation combined with strength training promote morphofunctional alterations? - Evangelista, Alexandre Lopes (2019)
OBJECTIVES: The aim of this study was to evaluate the effects of 8 weeks of strength training (ST) combined with whole-body electrical stimulation (EMS) on morphofunctional adaptations in active individuals. METHODS: Fifty-eight volunteers were randomly distributed into the following groups: an untrained control (UN) group (n=16), an ST group (n=21) or an ST combined with EMS (ST+EMS) group (n=21). Both intervention groups (the ST and ST+EMS groups) performed 3 exercises (biceps curl, back squats and high-pulley tricep extensions) twice a week for 8 weeks. The subjects performed 3 sets of 8 to 12 maximum repetitions (MRs) with a 90-second rest duration between sets. The ST+EMS group performed the resistance training exercises wearing a whole-body suit that provided electrical stimulation at frequencies between 80-85 Hz, with a continuously bipolar impulse duration and pulse breadth of 350 ms. The intensity for each muscle group was controlled by Borg’s category ratio (CR)-10 scale; the intensity started at 5-6 and eventually reached 7-8. One-repetition maximum strength (1RM) and muscle thickness (MT) were measured before and after the training intervention. MT was evaluated in the biceps brachii (BB), triceps brachii (TB), and vastus lateralis (VL). RESULTS: No differences (p40.05) were found between the ST and ST+EMS groups. Improvements (po0.05) in the absolute values of the morphofunctional parameters after the training protocol were observed. Significant differences were found between both the intervention groups and the UN group (po0.05). The ST+EMS group presented high percentage changes (po0.05) in muscular strength for the 1RMsquat (43.2%, ES=1.64) and the MT of the BB (21.6%, ES=1.21) compared to the ST (20.5%, ES=1.43, 11.9%, ES=0.77) group. CONCLUSIONS: Our data suggest that the combination of ST+EMS may promote alterations in muscle strength and MT in healthy active subjects.